2010
DOI: 10.1002/jor.21131
|View full text |Cite
|
Sign up to set email alerts
|

Median nerve deformation and displacement in the carpal tunnel during index finger and thumb motion

Abstract: The purpose of this study was to investigate the deformation and displacement of the normal median nerve in the carpal tunnel during index finger and thumb motion, using ultrasound. Thirty wrists from 15 asymptomatic volunteers were evaluated. Cross-sectional images during motion from full extension to flexion of the index finger and thumb were recorded. On the initial and final frames, the median nerve, flexor pollicis longus (FPL), and index finger flexor digitorum superficialis (FDS) tendons were outlined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
79
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(83 citation statements)
references
References 20 publications
4
79
0
Order By: Relevance
“…They observed movement of approximately 1.5 mm in healthy individuals and a smaller value in patients with CTS. Van Doesburg reported transverse sliding motion of 2 mm during active middle finger movements [4], whereas Hsieh reported that a gripping action caused the median nerve to enter between the flexor digitorum superficialis and flexor pollicis longus in the hands of healthy individuals, but not in patients with CTS [8]. The present results show that finger movements produced a mean transverse sliding motion of about 6.6 mm in healthy individuals, which was significantly less in patients with CTS (4.9 mm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed movement of approximately 1.5 mm in healthy individuals and a smaller value in patients with CTS. Van Doesburg reported transverse sliding motion of 2 mm during active middle finger movements [4], whereas Hsieh reported that a gripping action caused the median nerve to enter between the flexor digitorum superficialis and flexor pollicis longus in the hands of healthy individuals, but not in patients with CTS [8]. The present results show that finger movements produced a mean transverse sliding motion of about 6.6 mm in healthy individuals, which was significantly less in patients with CTS (4.9 mm).…”
Section: Discussionmentioning
confidence: 99%
“…In open carpal tunnel release surgery, the enlarged median nerve is recognized as a pseudoneuroma. The location and shape of the median nerve change with passive and active finger movements, and these changes can be observed in real-time with ultrasonography [2][3][4][5]. Toge et al [6] have further investigated median nerve motion in normal subjects during active flexion of each finger.…”
Section: Introductionmentioning
confidence: 99%
“…These deficiencies mainly include undeveloped supporting theory system of surrounding rock deformation, weak link of tunnel design and construction with geological conditions, low mechanization level of construction, and uncontrollable safety risk in complex geological conditions (Wang 2010). The mechanical properties and deformation control in the construction process of schist tunnels under complex geological environment are the frontier research topics in the field of tunnel projects (Lindenbergh et al 2005;Tsesarsky and Hatzor 2006;Van Doesburg et al 2010). Owing to schist is broken with poor quality, and B. Zhang (&) Á H. Hu Á S. Liang Á T. Niu Á Z. Guo Á G. Song Zhangjiakou Vocational and Technical College, Zhangjiakou 075000, Hebei, China e-mail: huh075@163.com shows large deformation volume and long deformation time, it is likely to be deformed significantly and even collapses in the excavation of tunnels.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, little research has examined in detail the specific location of the median nerve as a coordinate within the carpal tunnel, although several previous studies have used ultrasonography to evaluated the directions and vectors of the median nerve during finger motion 3,4,7,8 . Demonstrating the location of the median nerve as a coordinate helps provide a more accurate understanding of nerve orientation within the carpal tunnel, such as the start and end points of nerves during wrist and finger motion.…”
Section: Introductionmentioning
confidence: 99%
“…1 Ultrasound examination setup at the wrist neutral position of the median nerve at the wrist 3 8 . During movements of the fingers or wrist, the median nerve moves longitudinally and transversely in response to the motion of the adjacent tendons that move actively in the carpal tunnel 3,7,9 . Some studies using transverse ultrasonography have demonstrated that the median nerve is displaced palmarly in active finger flexion and becomes compressed between the transverse carpal ligament and the flexor tendons in both healthy persons and patients with CTS 3 7 .…”
Section: Introductionmentioning
confidence: 99%